The Weight of Aristophanes - Plato and the `Other' Comic Poets: An Intertextual Analysis of Plato's Protagoras and Eupolis' Kolakes - Strigel, William Mogens (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2024)
This thesis has two aims. The first is to reorient the scholarly norm when thinking about Plato in relation to the genre of Greek Comedy. Since modern scholarship started taking Plato’s relationship to comedy seriously as a means of analysing his work, it has been dominated by the thought and writings of Aristophanes, especially his extant Clouds. I aim to show that such scholarship has become overburdened by this figure. Socrates was a character of concern for many poets of the fifth century, those contemporary with Aristophanes. What, then, can or should we say about Plato’s reactions to the ‘other’ comic poets surrounding him both before and during his life—in the period of ‘Middle’ Comedy? I thus aim in this thesis to ‘lift the weight’ of Aristophanes from the standard scholarly procedure in the discourse on Plato’s intertextual dealings with comedy. I look first to the long-known reliance of the Protagoras upon Eupolis’ Kolakes (or Flatterers) in the service of such a task. To examine how Plato relied on Eupolis thereby forms the main content of this thesis. I argue the Kolakes furnished what was, in the 420s BCE, a faint distinction between the ethos of Socrates and those we typically call ‘sophists’. The former was a laconizing ascetic who, although a ‘thinker’ like the others, had no interest in food or luxuries but set his mind to chattering about speculative nonsense. The others were surreptitious gluttons, eager to dupe patrons with their ‘wisdom’ for corporeal pleasures. I argue that this distinction in comedy—tenuous as it may have originally been—was regarded by Plato as essentially correct and, for that reason, held it up for reflection, amplification, and transformation. In doing so, he created what I call the literary paradigm ‘philosopher and flatterer’ or ‘flatterer and philosopher’. The Protagoras in particular relies upon the Kolakes to do this for a host of philosophical ends (though not without incorporating other works and genres in the process). The first chapter shows how fifth century comedy produced this element of difference between Socrates and the sophists, one which offered literary-philosophical affordances to Plato. The second chapter begins to examine Plato’s appropriation of such affordances by examining the character of Protagoras in his titular dialogue in relation to his counterpart in the Kolakes and other flatterers in comedy. The third chapter argues that the Kolakes had a ‘competition in wisdom’ between two sophistic pairs. Eupolis, I argue, turned this competition into what one testimonium calls ‘a competition of flattery’. Plato relied to a certain extent on that competition in Eupolis when depicting Socrates and Protagoras locked in combat, starting (at least) with the debate over Simonidean lyric to the closing of the dialogue. And given that Socrates wins that debate, Plato (or his Socrates) at once explodes the convention of such competitions and adopts its traditional prize: the reputation for Delphic-sanctioned sage wisdom. This wisdom best explains not only the aporetic ending of the dialogue, but also Socrates’ ability to see through the souls of the sophists in the para-Homeric Nekyia. The fourth chapter argues that in the para-Nekyia of the Protagoras, the souls of flattering sophists are shown to suffer the same fate as the souls of flattering sophists in the Gorgias. I therefore argue that the two dialogues are metaphysically linked just in respect of the literary contrast ‘philosopher and flatterer’. The fourth chapter shows how Socrates in the Protagoras is also reminiscent of his character in the Gorgias and how he is redolent of his persona as a laconizing chatterer in comedy. Thus, the Protagoras, as well as other dialogues, are built around a motif that had an evidently irresistible shape and role both in the Kolakes and elsewhere in comedy to structure his philosophical worldview. The thesis concludes with suggestions as to where to go next in reorienting how we should think about Plato in his comic world, both Old and Middle. Through an analysis of Eupolis’ Demes and other works, I argue that the poet had a philosophical acumen which was highly conducive to Plato’s own philosophical purposes—thus suggesting the utility of future inquiries into ‘Eupolidean appropriations’. I also argue we should look towards ‘the Sicilian connection’ the dialogues had to Dionysius I of Syracuse, for whom I argue the Protagoras was written. I close with an argument that the ‘Digression’ of the Theaetetus is Plato’s response to depictions of himself and the Academy on the Middle Comic stage. With these arguments in hand, I hope to go some distance in ‘lifting the weight’ of Aristophanes, as it were, and helping others to do so in future as well.
APPROVED
Keywords: Greek Comedy; Old Comedy; Middle Comedy; Socrates; Sophists; Plato; Aristophanes; Eupolis; Protagoras; Gorgias